Clinical outcome of patients with diabetes mellitus infected by SARS-COV-2 - Barros, Nara Regina Batista; Mascarenhas, André Neves; Barros Junior, Francisco de Souza; Barros de Vasconcelos, Beatriz; Sousa, Tainá Maria Oliveira; Carvalho, Ana RaquelBatista de (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Diabetes, a chronic metabolic disease with high prevalence in Brazil, is a risk factor for severe SARS COV-2 infection. The relationship between previous glycemic control and the prognosis of patients hospitalized with COVID-19 is not fully understood. Objective: analyze the clinical outcome of patients with diabetes mellitus infected by SARS-COV-2. Outlining: A retrospective analysis of medical records was carried out using the Trakcare electronic system of all diabetic patients hospitalized with a confirmatory diagnosis of pneumonia due to COVID-19 in the medical clinic ward of HRAN, from June to August 2021, who, upon admission, performed the glycated hemoglobin test and analyzed it using the SPSS software (20.0). Results: A sample of 52 patients was obtained during the study period. Most patients are female, with a mean age of approximately 58 years. The comorbidity most associated with the participants was systemic arterial hypertension, with most diabetics presenting good prior glycemic control, represented by HbA1c ≤ 7%. The lethality found was 7.7%. Implications: The study shows a high lethality of diabetic patients infected by COVID 19, but no statistical significance was found for HbA1c levels with the increase in length of stay, use of non-rebreathing mask, need for invasive mechanical ventilation or lethality